A portfolio-balance approach to the nominal term structure - Thomas B. King (Federal Reserve Bank of Chicago, 2013)
Explanations of why changes in the relative quantities of safe debt seem to affect asset prices often appeal informally to a portfolio balance mechanism. I show how this type of effect can be incorporated in a general class of structural, arbitrage-free asset-pricing models using a numerical solution method that allows for a wide range of nonlinearities. I consider some applications in which the Treasury market is isolated, investors have mean-variance preferences, and the short-rate process is truncated at zero. Despite its simplicity, a version of this model incorporating inflation can fit longer-term yields well, and it suggests that fluctuations in Treasury supply explain a sizeable fraction of the historical time-series variation in term premia. Nonetheless, under plausible parameterizations central-bank asset purchases have a fairly small impact on the yield curve by removing duration from the market, and these effects are particularly weak when interest rates are close to their zero lower bound.
Keywords: C63; E43; E44; E52; E58; G11; G12; 330; Yield curve; LSAP; quantitative easing; preferred habitat; forward guidance